A Semiotic Analysis on Emotional Aspect of Bruno Mars feat Lady Gaga’s Song “Die with a Smile” in YouTube - Setiadi, Christopher (JELT: Journal of English Language Teaching, 2025)
Music is one of a type of instrument that people like to hear nowadays. Inside of music, there is also a part of a lyric that combined together in one of a song which can bring a meaning to its listeners.  Furthermore, this lyric also can be explained by an analysis using a linguistics approach and one of that is a semiotics. In here, the semiotics aspect can be used by a theory from Roland Barthes which is he has three approaches to analyze it in form of semiotics aspect: denotation, connotation, and myth. In this study, the researcher using a song titled “Die with a Smile”, sung by Bruno Mars feat Lady Gaga that is popular among society in a YouTube platform and analyze its lyrics to find an emotional aspect meaning behind its song. In this study, the researcher uses a method of qualitative descriptive. For the data analysis, the data consists of the lyrics that are separated into 5 parts and each part will analyze its denotation and connotation. Afterwards, the researcher find its myth aspect which is related with an emotional aspect that occur in the lyrics. The result of this research occurs that from 5 parts of the lyrics that already analyzed using Roland Barthes semiotics theory, almost of that parts contain of emotional aspect in love and someone the person that one caring which is very important to his or her life.